Zn-Al and Mg-Al layered double hydroxides as nanostructured carriers for vitamins - Foraida, Zahraa Ismail Ahmed (AUC Knowledge Fountain, 2013)
Layered double hydroxides (LDHs) are a group of natural and synthetic materials. They are structured as positively-charged layers mostly of divalent-trivalent metal combination between which anions are embedded. The container-like structure and the feasibility to vary the metallic and the interlayer components attracted attention to their use as potential carriers for biologically-active compounds for purposes such as preservation and storage, modulation of release, improving the solubility, targeted delivery, etc. This study aims at investigating the possibility to load different vitamins having different chemical characters into Zn-Al and Mg-Al LDHs of nitrate precursors, characterizing the produced vitamin-LDH hybrids and studying their release behavior. The preparation methods used entailed the co-precipitation and ion-exchange methods for the Zn-Al LDH and the co-precipitation, ion-exchange and reconstruction methods for the Mg-Al LDH system. Characterization of the pristine LDHs and the vitamin-LDH hybrid systems was carried out using XRD, FTIR, SEM and the interlayer arrangements of the vitamins were proposed. The loaded amount and release behavior were studied using UV spectroscopy. The characterization results indicated successful intercalation of vitamin B2 (medium to large neutral molecule) into Zn-Al and Mg-Al LDH systems by the co-precipitation method only, with loading amounts ≈ 55.1 and 53.2 (%w/w) respectively. The release from the Zn-Al system was more sustained where complete release was not reached within 20 minutes. The intercalation of vitamin B6 (small anionic molecule) was successful for all trials: co-precipitation and ion-exchange for Zn-Al LDH, with loading amounts ≈ 16.3 and 38.9 (%w/w), and co-precipitation, ion-exchange and reconstruction for Mg-Al LDH, with loading amounts ≈ 12.9, 17.2, 13.8 (%w/w). The release of the two B6-Zn-Al hybrid systems was more sustained (not complete within the 20-minute study period) with biphasic release observed for the anion-exchanged sample due to the intercalation of the vitamin adopting two different interlayer arrangements. On the other hand, complete release was noticed for the B6-Mg-Al hybrid systems within 15 minutes at most. Folic acid was successfully intercalated into Zn-Al LDH using the co-precipitation and ion-exchange methods with loading amounts of 36.5 and 36 (%w/w) respectively, while it failed for the Mg-Al LDH system by all routes. The release of the co-precipitated Zn-Al hybrid system was biphasic and significantly sustained with the release of only 50% of the intercalated vitamin within 20 minutes. This is attributed to the orientation of folic acid within the LDH layers promoting strong attractive forces with the LDH environment and hence hindering the immediate release. On the other hand, the ion-exchanged Zn-Al hybrid showed complete release within 10 minutes. Vitamin C was loaded into Zn-Al and Mg-Al LDHs by the co-precipitation and ion-exchange methods with loading amounts of 38 and 13 (% w/w) for the co-precipitated and ion-exchanged Zn-Al LDH hybrids respectively, 6 and 21.5 (% w/w) for the co-precipitated and ion-exchanged Mg-Al LDH hybrids respectively, while the intercalation failed by the reconstruction method. The release of the Zn-Al hybrid systems was more sustained and followed a biphasic behavior, while that of the Mg-Al hybrid systems was faster and reached completion in shorter time periods. In general, the intercalated vitamin amount was higher for the Zn-Al LDH systems as the Zn is more electronegative than Mg leading to more attraction between the LDH layers and the guest molecules. In addition, the release behavior depended on the vitamin-LDH interactions, as the attractive forces increased, the release was more sustained. Intercalation of vitamin B1 and B5 was unsuccessful for all trials: co-precipitation and ion-exchange to the Zn-Al LDH and co-precipitation, ion-exchange and reconstruction to the Mg-Al LDH system. In conclusion, nanostructured biocompatible LDH carriers for vitamins B2 , B6, folic acid and vitamin C were successfully synthesized using different methods. They showed significant vitamin loading and feasible release suggesting their potential use as vitamin storage carriers and delivery systems.